Inmunocastración en porcinos (Sus scrofa domesticus): Un enfoque bibliográfico - Flores Campozano, Oscar Niali (2023)
Immunocastration is a viable and animal welfare friendly alternative to surgical castration, knowing that this technique is mostly performed without anesthesia and analgesia, bringing with it a series of consequences such as: post-surgical effects, growth disorder and sometimes death of the animal; based on this background, the present study was conducted in order to analyze the technique of immune castration, to know its applicability and to compare its efficiency at the productive level. For this purpose, a great variety of information was compiled regarding the investigations focused on this topic of "immunocastration in pigs (Sus scrofa domesticus)", which allowed describing the technique, its advantages and benefits at an economic level. It is important to point out that mortality levels increase in pigs surgically castrated at an early age, so immunocastration is an innovative technique for the reduction of economic losses; in addition, the use of this technique has shown to guarantee positive results in zootechnical indicators. Likewise, it is highlighted that its application has a lower environmental impact because it reduces the generation of residues and decreases the use of anesthetic and analgesic drugs, thus reducing production costs. It is considered that this technique will be used by most producers in the future, since it is a very promising procedure, eliminating boar taint in pork meat without compromising growth and meat quality.